Exploring Social Media Use Integration Based on Educational Level Among Emerging Adults - Vania Ardelia; Siti Jaro'ah (International Journal of Current Educational Research, 2023)
Objective: Social media has become integral to everyday life, including among emerging adults. Surveys showed that Instagram has become one of emerging adults' most popular social media. Social media could facilitate emerging adult developmental tasks, such as identity exploration. Further, social media uses integration concepts to explore how individuals build emotional connections and involve social media in their daily social routines. Additionally, it is essential to view social media use integration based on educational background. This study explored differences in social media use integration among emerging adults based on education level. Method: A cross-sectional study design was conducted among 305 men and women emerging adults. Participants completed a self-administered questionnaire comprising demographic characteristics and a Social Media Use Integration scale. Data were analyzed using descriptive analysis and one-way ANOVA statistic technique. Results: Descriptive analysis results showed that individuals with a high school education level had the highest social media use integration scores compared to groups from other education levels. Further, education level notably contributed to the score difference in social media use integration among emerging adults. Novelty: This study contributed to exploring further the social media use integration among emerging adults, specifically in the context of educational background.